Progressive collapse analysis of corner-supported composite modular buildings. (1st May 2022) - Peng, Jiahao; Hou, Chao; Shen, Luming
Abstract: In this study, the alternate load path analysis is carried out to investigate the progressive collapse resistance of multi-storey modular buildings constructed using corner-supported composite modules. Three sudden column loss scenarios are considered: a corner column, an edge column at the long side, and an edge column at the short side. The non-linear dynamic analysis is first conducted to investigate the peak dynamic response of the locally damaged structures. The dynamic analysis results show that the 4-storey building prototypes remain elastic whilst partial yield in the joint regions is developed in the 12-storey counterparts; however, no collapsing tendency has been observed in cases under design loads. In the non-linear static analysis, the capacity curve and the overload factor for each case are then identified by increasing the gravity load until failure occurs. Four possible failure mechanisms are identified, varying among the different column loss scenarios and the building height. The suitable dynamic increase factors (DIFs) for the proposed composite modular buildings are identified on the basis of achieving the same maximum vertical displacement at the point of column removal when the non-linear static method is carried out to predict the peak dynamic response to sudden column removal. The DIFs of 1.90 and 1.60 are recommended for the 4- and 12-storey modular buildings, respectively. Highlights: Progressive collapse of multi-storey modular buildings is studied at sudden column loss scenarios. Alternate load paths can be activated after the notional column removals. Four distinctive failure mechanisms after the sudden column losses are identified. Dynamic increase factors of 1.9 and 1.6 are recommended for the 4- and 12-storey buildings.